Effect of leukocyte and platelet rich fibrin (L-PRF) on stability of dental implants. A systematic review and meta-analysis. Issue 10 (December 2021) - Lyris, V.; Millen, C.; Besi, E.; Pace-Balzan, A.
Abstract: The aim of this study was to assess the impact, if any, of L-PRF application in an implant bed prior to implant placement, focusing on stability by means of implant stability quotient (ISQ) values. The literature was searched in a systematic way by means of the main databases and hand searching of the most relevant journals. The inclusion and exclusion criteria were used to determine the eligible studies included in this review. Only randomised controlled trials (RCT) and controlled clinical trials (CCT) were included. A total of four RCTs were included for data extraction. The risk of bias was deemed moderate to unclear. Meta-analysis was performed to assess the effect of L-PRF, on implant stability, immediately post-insertion in three studies, after one week from the implant placement in three studies and after four weeks for all the included studies. The fixed effects model has shown Hedges g statistic for the one week varying from 0.380 to 1.401 with a pooled figure of 0.764 (95% CI 0.443 to 1.085) and for four weeks varying between 0.74 and 1.1 with a combined effect of 0.888 (95% CI 0.598 to 1.177). The results for both intervals were in favour of the use of L-PRF while the statistical difference immediately post-insertion was not statistically significant. The present systematic review, though acknowledging its limitations, suggests that L-PRF has a positive effect on secondary implant stability and that needs to be correlated to the clinical practice to measure the actual clinical effect by means of reducing treatment times.